2017
DOI: 10.1007/s11926-017-0646-8
|View full text |Cite
|
Sign up to set email alerts
|

In the Pursuit of Methotrexate Treatment Response Biomarker in Juvenile Idiopathic Arthritis—Are We Getting Closer to Personalised Medicine?

Abstract: No clinical biomarker that would predict the outcome of MTX therapy exists. Results of several studies focused on gene polymorphisms and outcome of this DMARD therapy have been published, but no reliable genetic marker useful to tailor the therapy has been discovered so far. The results of the first genome-wide association study in this field have recently revealed new genetic candidates from outside the metabolic pathway of MTX that may be associated with the efficacy of treatment. However promising, those ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…However, a GWAS study found no direct correlation between SNPs related to the pathways of MTX and the efficacy in 759 JIA patients (Cobb et al, 2014). This suggests that SNPs may not necessary in revealing the outcome of JIA (Albers et al, 2009; Roszkiewicz and Smolewska, 2017). Moreover, the expression and activity of enzymes in children may be affected by growth, and the genotype may not directly reflect the phenotype (Zhao et al, 2010; Roszkiewicz and Smolewska, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, a GWAS study found no direct correlation between SNPs related to the pathways of MTX and the efficacy in 759 JIA patients (Cobb et al, 2014). This suggests that SNPs may not necessary in revealing the outcome of JIA (Albers et al, 2009; Roszkiewicz and Smolewska, 2017). Moreover, the expression and activity of enzymes in children may be affected by growth, and the genotype may not directly reflect the phenotype (Zhao et al, 2010; Roszkiewicz and Smolewska, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Rheumatoid vasculitis, a relatively rare condition, can affect the aorta. This condition is difficult to discriminate clinically from atherosclerosis 6 . Furthermore, RA is associated with significant inflammation and an elevated cardiovascular risk and mortality comparable to that of diabetes 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, determinants of early MTX response and toxicity that can be applied to individualize JIA treatment strategies are urgently required. There is growing evidence 4 that single nucleotide polymorphisms (SNP) within the genes responsible for MTX cellular influx/efflux, polyglutamination, involved in folate pathway, purine and pyrimidine synthesis (Figure 1) are associated with response to the drug and risk of therapy adverse events (AE), both in patients with rheumatoid arthritis (RA) 5‐7 and JIA 8 . Despite its widespread use, the mechanism of action of low‐dose MTX used weekly in rheumatological indications remains elusive 9 .…”
Section: Introductionmentioning
confidence: 99%